68.6k views
4 votes
F(x)=3x+5

G(x)=4x^2-2
H(x)=x^2-3x+1
Find f(x) + g(x)-h(x)
A.6x^2+6x-1
B.5x^2+4
C.3x^2+2
D.3x^2+6x+2

F(x)=3x+5 G(x)=4x^2-2 H(x)=x^2-3x+1 Find f(x) + g(x)-h(x) A.6x^2+6x-1 B.5x^2+4 C.3x-example-1
User Axlotl
by
6.1k points

2 Answers

4 votes

Answer:

it's a D

Explanation:

3x^2+6x+2

User Nik Shenoy
by
5.6k points
3 votes

Answer:

Explanation:

F(x) = 3x + 5

G(x) = 4x^2 - 2

H(x) = x^2 - 3x + 1

F(x) + G(x) - H(x) =

3x + 5 + 4x^2 - 2 - (x^2 - 3x + 1) =

3x + 5 + 4x^2 - 2 - x^2 + 3x - 1 =

3x^2 + 6x + 2 <===== ur answer

User YYashwanth
by
5.5k points